Любовь и долг: [роман] / Семен Малков - Малков Семен Наумович (Гелеос, 2006)
Экземпляры: аб. ЦБ (2017.14.12) / Инвентарный номер: 3686 / Цена: 80.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М 19 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6